If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -27 = 6x + 3 Reorder the terms: -27 + 12x = 6x + 3 Reorder the terms: -27 + 12x = 3 + 6x Solving -27 + 12x = 3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -27 + 12x + -6x = 3 + 6x + -6x Combine like terms: 12x + -6x = 6x -27 + 6x = 3 + 6x + -6x Combine like terms: 6x + -6x = 0 -27 + 6x = 3 + 0 -27 + 6x = 3 Add '27' to each side of the equation. -27 + 27 + 6x = 3 + 27 Combine like terms: -27 + 27 = 0 0 + 6x = 3 + 27 6x = 3 + 27 Combine like terms: 3 + 27 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| -56-7x=8x+19 | | 2x+77=8x+11 | | 7+2=11 | | 12x+77=9x+23 | | 93-3x=2x+18 | | -54-3x=6-9x | | 118-4x=14x+16 | | x^2-14x+3=0 | | 13-9x=78-44x | | -61-10x=10x+19 | | 3x+14=-46-7x | | 96-4x=2x+12 | | -7-5x=8-10x | | x^2+10x+2=0 | | -7(2p+3)-49=4(4p+5) | | -7x=91 | | -7=91 | | x-1.2=-4.5+2.3 | | 2x=7x | | 6x-3=15x-57 | | x(x+1)=3x-10 | | 0=-8(Y+4) | | 3(C-4)=4(C-5) | | 7-8c=19-2c | | 10=5x-10 | | 5x+3=7x-5(2x+1) | | x^2-6x=27 | | x^2+20x=0 | | x(x+1)=0 | | -4(2x+5)= | | 5a-3=3a+9 | | 3a+2=a+12 |